Antimicrobial Resistance Profiles and Macrolide Resistance Mechanisms of Campylobacter coli Isolated from Pigs and Chickens - Ji-Hyun Choi; Dong Chan Moon; Abraham Fikru Mechesso; Hee Young Kang; Su-Jeong Kim; Hyun-Ju Song; Soon-Seek Yoon; Suk-Kyung Lim (Microorganisms, 2021)
We identified 1218 Campylobacter coli isolates from fecal and carcass samples of pigs (n = 643) and chickens (n = 575) between 2010 and 2018. About 99% of the isolates were resistant to at least one antimicrobial agent. The isolates exhibited high resistance rates (>75%) to ciprofloxacin, nalidixic acid, and tetracycline. Azithromycin and erythromycin resistance rates were the highest in isolates from pigs (39.7% and 39.2%, respectively) compared to those of chickens (15.8% and 16.3%, respectively). Additionally, a low-to-moderate proportion of the isolates were resistant to florfenicol, gentamicin, clindamycin, and telithromycin. Multidrug resistance (MDR) was found in 83.1% of the isolates, and profiles of MDR usually included ciprofloxacin, nalidixic acid, and tetracycline. We found point mutation (A2075G) in domain V of the 23S rRNA gene in the majority of erythromycin-resistant isolates. Multilocus sequence typing of 137 erythromycin-resistant C. coli isolates revealed 37 previously reported sequence types (STs) and 8 novel STs. M192I, A103VI, and G74A substitutions were frequently noted in the ribosomal proteins L4 or L22. Further, we identified a considerable proportion (>90%) of erythromycin-resistant isolates carrying virulence factor genes: flaA, cadF, ceuE, and VirB. The prudent use of antimicrobials and regular microbiological investigation in food animals will be vital in limiting the public health hazards of C. coli in Korea.